Method for preparing 700 DEG C-resistant high-performance titanium-based composite material by using selective laser melting technology
Through the combination of laser selection melting technology and ceramic reinforced phase, the problem of difficult to take into account both the formability and high-temperature performance of titanium-based composite materials in traditional methods is solved, and a high-performance titanium-based composite material with a 700℃ resistance is prepared to meet the high temperature in the aerospace field. Material requirements.
Patent Information
- Application Number
- CN202411270560.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The process of preparing high-temperature resistant titanium-based composite materials in traditional methods is complicated and complex, and the forming is difficult to combine the formingability and high-temperature performance in the 3D printing process, which cannot meet the demand for high-temperature materials in the aerospace field.
Using laser selection melting technology, TC11 alloy with both thermal strength and formability is selected as the matrix, high-strength ceramic particle reinforcement phase is added, reasonable printing model and process parameters are designed, and process parameters are optimized through annealing heat treatment to prepare good Titanium-based composite material with formability and high temperature mechanical properties.
It realizes efficient and near-net forming complex components, improves the room temperature and high temperature tensile strength, elongation, and the heat resistance temperature reaches 700℃, meeting the high temperature performance needs in the aerospace field.
Smart Images

Figure CN119114970A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of alloys, and in particular relates to a method for preparing a 700°C-resistant high-performance titanium-based composite material by using a laser selective melting technology. Background Art
[0002] High-temperature titanium alloy is a key material in the structural materials of my country's aerospace field. With its low density, high specific strength, good high-temperature performance and corrosion resistance, it is widely used in the aerospace field and has developed rapidly. It is called the backbone of the aviation industry. Because aircraft engines have stringent performance requirements for high-temperature titanium alloys, the material is required to have good room temperature performance, high-temperature strength, creep performance, thermal stability, fatigue performance and fracture toughness. However, the requirements of various performance indicators on the composition and organization of the material are contradictory. For example, room temperature toughness and high-temperature strength are inverted. Laser selective melting additive manufacturing technology can achieve near-net forming of complex metal components, and has great advantages in improving forming dimensional accuracy, preparation efficiency and material utilization. Although there are many high-temperature titanium alloys, such as TA15, TC31, Ti55, Ti60, Ti65, Ti600, etc., which can be used at temperatures up to 500℃-600℃, they usually show an inverted relationship between the thermal strength of the material and the formability of laser selective melting. For example, the 600℃ high-temperature titanium alloy Ti60 is not suitable for laser selective melting with extremely fast cooling rate, and is prone to macro cracking and poor formability. TA15 titanium alloy has good formability by laser selective melting, but the long-term working temperature is only 500℃, which is difficult to meet the requirements of high-speed aircraft thermal protection components for the material's temperature bearing capacity, and the high-temperature mechanical properties need to be improved urgently.
[0003] Additive manufacturing technology, with its unique advantages of full digitalization without mold opening, fast solidification speed and near-net-shape forming of complex parts, is increasingly widely used in the demonstration and application of structural and functional parts in the aerospace field, providing a new method with great potential for the preparation of metal-based composite materials.
[0004] In the process of preparing high-temperature resistant titanium-based composite materials using laser selective melting additive manufacturing technology, although introducing a certain amount of reinforcing phase by mixing powders can refine the grains, eliminate coarse columnar crystal textures, and thus improve the thermal strength and service temperature of the material, it also increases the difficulty of forming the material. Since the melting and solidification process of additive manufacturing is accompanied by rapid temperature changes, uneven plastic deformation caused by thermal expansion and contraction or solid-state phase change is prone to occur inside the sample, so there is often a large residual stress, resulting in macro cracking and other phenomena; when the selected printing parameters such as energy density are inappropriate, defects such as cracking or porosity are also prone to occur, which ultimately makes it difficult to balance the formability and high-temperature performance of titanium-based composite materials, and further stabilize the microstructure through subsequent heat treatment. Summary of the invention
[0005] The purpose of the present invention is to solve the problems that the traditional preparation and processing processes of high-temperature resistant titanium-based composite materials are cumbersome and complicated, and the forming of complex components is difficult, as well as the problem that it is difficult to balance the formability and high-temperature performance of titanium-based composite materials during 3D printing. A method for preparing high-performance titanium-based composite materials resistant to 700°C by using laser selective melting technology is provided.
[0006] At present, the traditional methods for preparing high temperature resistant titanium-based composite materials include melting casting, powder metallurgy, etc., which have complicated processing procedures, long cycles, low material utilization rate, and high difficulty in processing complex shaped components. The laser selective melting technology used in the present invention has strong comprehensive functions, can reduce assembly time, improve material utilization rate, save direct costs, and thus achieve near-net shape of complex components with high efficiency and high quality.
[0007] At present, the heat resistance of high-temperature titanium alloys and high-temperature resistant titanium-based composite materials prepared by laser selective melting can no longer meet the demand for structural materials in high-precision fields such as aerospace. The present invention selects TC11 alloy with both thermal strength and formability as the matrix, adds high-strength ceramic particles to strengthen the phase and designs its content, adjusts ball milling parameters, designs the shape of the printing model, optimizes printing parameters, and performs annealing heat treatment to prepare a high-temperature resistant titanium-based composite material with good formability. A high-performance titanium-based composite material resistant to 700°C is prepared, breaking through the bottleneck of the use of previous materials at 600°C.
[0008] In response to the above needs, the present invention proposes a titanium-based composite material with both high temperature resistance and good laser selective melting formability. By selecting α+β type medium temperature titanium alloy-TC11 powder as the matrix, the nominal composition of the alloy is Ti-6.5Al-3.5Mo-1.5Zr-0.3Si, and its service temperature can reach 500°C. It contains a high content of Mo element, which ensures the plasticity and laser selective melting formability of the alloy. In addition, because it contains Si element, it is beneficial to improve the thermal strength of the material. On this basis, ceramic powders such as TiB2 are further introduced to react with Ti in situ to generate ceramic reinforcement phases such as TiB, and the high temperature mechanical properties are further improved through the strengthening effect, and the heat resistance temperature reaches 700°C.
[0009] The present invention selects medium-temperature titanium alloy TC11 as the matrix and high-modulus TiB and other ceramic whiskers as reinforcements. By optimizing the laser selective melting manufacturing parameters and subsequent heat treatment parameters, a lightweight titanium-based composite material with good formability, excellent high-temperature mechanical properties and high-temperature stability is prepared. The heat-resistant temperature reaches 700°C, which can better meet the use requirements.
[0010] The present invention has the following beneficial effects:
[0011] (1) The present invention adds TiB2 ceramic phase to TC11 alloy, and reacts with Ti to form TiB reinforcing phase in situ, presenting a unique network structure distribution of hard phase surrounding soft phase, thereby improving strength. Then, the ball milling parameters and reinforcing phase content are further optimized, and finally a TiBw / TC11 composite material powder with an optimal TiB2 content of 0.6wt.% is obtained. The printed composite material has been tested and the room temperature tensile strength reaches 1627MPa (such as Figure 4 As shown), the room temperature tensile strength of the printed TC11 alloy under the same printing parameters is 1475MPa, which is 10% higher than that (as shown Figure 3 shown).
[0012] (2) TiBw / TC11 composite materials are prone to macroscopic cracking during selective laser melting preparation due to the extremely high cooling rate and temperature gradient, and have extremely poor formability. The present invention combines multiple methods in the selective laser melting process to directly obtain components without macroscopic cracking and with low residual stress - that is, by regulating the substrate preheating temperature, optimizing the process parameters, optimizing the structural design of the formed component, and the subsequent annealing heat treatment process, the macroscopic cracking phenomenon is effectively avoided, and a high-temperature resistant titanium-based composite material (such as titanium-based composite material) with good formability and high density is obtained. Figure 1-2 shown).
[0013] (3) After annealing heat treatment, the composite material prepared by the present invention has a room temperature tensile strength of ≥1200MPa and an elongation of ≥10%; a tensile strength of ≥450MPa at 700℃; and creep performance: a duration of ≥2h at 700℃ and 200MPa tensile stress. TC11 alloy and TiB / TA15 composite materials were prepared using the same process parameters. The tensile strength of TC11 alloy at 700℃ was 313MPa, an increase of 44%; the tensile strength of TiB / TA15 composite material at 700℃ was 342MPa, an increase of 32%. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Macro cracking photo of partially printed TiB / TC11 composite material before process optimization (square size: 45×15×15mm);
[0015] Figure 2 Macroscopic photos of some printed and heat-treated TiB / TC11 composite materials after process optimization (square size: 45×15×15mm);
[0016] Figure 3 Room temperature tensile properties of printed TC11 alloy;
[0017] Figure 4 Room temperature tensile properties of printed TiB / TC11 composites;
[0018] Figure 5 Annealed TC11 alloy 700℃ high temperature tensile properties diagram;
[0019] Figure 6 700℃ high temperature tensile properties of annealed TiB / TA15 composite material;
[0020] Figure 7 Room temperature tensile properties of annealed TiB / TC11 composites;
[0021] Figure 8 700℃ high temperature tensile properties of annealed TiB / TC11 composite materials;
[0022] Fig. 9 High temperature creep curve of annealed TiB / TC11 composite material under 700℃ / 200MPa conditions. DETAILED DESCRIPTION
[0023] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.
[0024] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention but are not intended to limit the present invention.
[0025] Example 1
[0026] This embodiment is carried out according to the following steps:
[0027] (1) (α+β) dual-phase medium-temperature titanium alloy—TC11 spherical powder was selected as the printing raw material. The nominal composition of the alloy was Ti-6.5Al-3.5Mo-1.5Zr-0.3Si, and the particle size distribution range was 15-53 μm.
[0028] (2) The alloy powder is placed in a vacuum drying oven, and the drying temperature is set to 120°C and the drying time is set to 4 hours, so as to eliminate the static electricity of the powder after ball milling, fully dry the powder, and improve the powder fluidity.
[0029] (3) Design and construct a three-dimensional model, import it into the model processing software corresponding to the printer, and place the model in the appropriate position as required.
[0030] (4) The dried powder was manufactured by selective laser melting process. The forming process was carried out in an argon protective atmosphere. The forming process window was: laser power 185 W, scanning power 1100 mm / s, powder layer thickness 30 μm, laser scanning interval 90 μm, and substrate preheating temperature 180 °C.
[0031] (5) The printed TC11 alloy was obtained by laser selective melting, and a subsequent annealing heat treatment was performed to control the variables. The temperature was set to 900°C, the holding time was set to 2 h, and the furnace was cooled to room temperature after the annealing was completed.
[0032] The room temperature mechanical properties of the printed TC11 alloy in this embodiment are as follows: the tensile strength is 1475 MPa (such as Figure 3 As shown); high temperature mechanical properties of annealed TC11 alloy: 700℃ tensile strength reaches 313.27MPa, elongation is 23.69% (as shown Figure 5 shown).
[0033] Example 2
[0034] This embodiment is carried out according to the following steps:
[0035] (1) A near-α titanium alloy TA15 is selected as the matrix, with a particle size distribution range of 15-53 μm. It has a high heat resistance temperature (500-550°C) and good high-temperature performance; and titanium diboride (chemical formula TiB2) powder is selected as the raw material for component modification, with a particle size of 0.5 μm.
[0036] (2) Spherical TA15 titanium alloy powder and TiB2 powder raw materials are mixed in a certain proportion, and the mass fraction of TiB2 powder accounts for 0.5wt.% of the mass fraction of the mixed powder. The mixed powder is subjected to low-energy ball milling under argon protection, with the ball-to-material ratio set to 2:1, the ball milling speed set to 220r / min, and the ball milling time set to 5h.
[0037] (3) The ball-milled mixed powder is placed in a vacuum drying oven, and the drying temperature is set to 120°C and the drying time is set to 4 hours, so as to eliminate the static electricity of the ball-milled powder, fully dry the powder, and improve the powder fluidity.
[0038] (4) Design and construct a three-dimensional model, add chamfers and other structural designs to prevent the sample from cracking, and then import it into the model processing software corresponding to the printer to place the model in the appropriate position as needed.
[0039] (5) The dried powder was manufactured by selective laser melting process. The forming process was carried out in an argon protective atmosphere. The forming process window was: laser power 180 W, scanning power 1100 mm / s, powder layer thickness 30 μm, laser scanning interval 90 μm, and substrate preheating temperature 180 °C.
[0040] (6) A 0.5wt.% TiB / TA15 titanium-based composite material was obtained by laser selective melting, and a subsequent annealing heat treatment was performed to eliminate residual stress. The temperature was set to 900°C and the insulation time was set to 2h. After the annealing was completed, the furnace was cooled to room temperature.
[0041] The annealed TiB / TA15 titanium-based composite material in this embodiment has been tested to obtain its high-temperature mechanical properties: the tensile strength at 700°C is 342 MPa, the elongation is 32% (such as Figure 6 shown).
[0042] Example 3
[0043] This embodiment is carried out according to the following steps:
[0044] (1) A (α+β) dual-phase medium-temperature titanium alloy, TC11 spherical powder, was selected as the matrix. The nominal composition of the alloy was Ti-6.5Al-3.5Mo-1.5Zr-0.3Si, and the particle size distribution range was 15-53 μm. Titanium diboride (chemical formula TiB2) powder was selected as the raw material for component modification, and the particle size was 0.5 μm.
[0045] (2) Spherical TC11 titanium alloy powder and TiB2 powder raw materials are mixed in a certain proportion, and the mass fraction of TiB2 powder accounts for 0.6wt.% of the mass fraction of the mixed powder after mixing. The mixed powder is subjected to low-energy ball milling under argon protection, with the ball-to-material ratio set to 2:1, the ball milling speed set to 200r / min, and the ball milling time set to 5h.
[0046] (3) The ball-milled mixed powder is placed in a vacuum drying oven, and the drying temperature is set to 120°C and the drying time is set to 4 hours, so as to eliminate the static electricity of the ball-milled powder, fully dry the powder, and improve the powder fluidity.
[0047] (4) Design and construct a three-dimensional model, add chamfers and other structural designs to prevent the sample from cracking, and then import it into the model processing software corresponding to the printer to place the model in the appropriate position as needed.
[0048] (5) The dried powder was manufactured by selective laser melting process. The forming process was carried out in an argon protective atmosphere. The forming process window was: laser power 185 W, scanning power 1100 mm / s, powder layer thickness 30 μm, laser scanning interval 90 μm, and substrate preheating temperature 180 °C.
[0049] (6) A 0.6wt.% TiB / TC11 titanium-based composite material was obtained by laser selective melting, and a subsequent annealing heat treatment was performed to eliminate residual stress. The temperature was set to 900°C and the holding time was set to 2h. After the annealing was completed, the furnace was cooled to room temperature.
[0050] The room temperature mechanical properties of the printed 0.6wt.% TiB / TC11 titanium-based composite material in this embodiment are as follows: tensile strength 1627MPa, elongation 0.62% (such as Figure 4The room temperature mechanical properties of the annealed TiB / TC11 titanium-based composite material were tested as follows: tensile strength 1213.53 MPa, elongation 10% (as shown). Figure 7 High temperature mechanical properties: 700℃ tensile strength reaches 452.34MPa, elongation is 13.53% (as shown); Figure 8 ); the endurance time under 700℃ and 200MPa is 2.2h (as shown in Fig. 9 As shown). It can be seen from the results that the in-situ self-generated TiB / TC11 titanium-based composite material prepared by the present invention by low-energy ball milling of TiB2 ceramic powder and TC11 titanium alloy and then laser selective melting technology has improved room temperature and high temperature tensile properties, effectively increasing the heat resistance temperature of the material to 700°C, while also ensuring good laser selective melting formability, and can achieve near-net forming of complex precision components.
Claims
1. A method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology. Features The method described is carried out as follows: (1) Titanium alloy TC11 powder was used as the matrix for preparing high-temperature titanium-based composites by laser selective melting, and ceramic powder was used as the raw material for component modification; (2) mixing titanium alloy TC11 powder and ceramic powder by low-energy ball milling under an argon atmosphere to obtain a composite powder; (3) placing the composite powder in a vacuum drying oven and fully drying it; (4) designing and constructing a three-dimensional model, setting printing parameters and printing strategies, preheating the printing substrate, and printing with the dried composite powder in an argon protective atmosphere; (5) The printed titanium-based composite material is taken out for annealing heat treatment. After the annealing is completed, the furnace is cooled to room temperature.
2. A method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1, Features The titanium alloy TC11 is an α+β dual-phase medium-temperature titanium alloy TC11.
3. A method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1 or 2, Features The titanium alloy TC11 powder is nearly spherical and has a particle size of 15-53 μm.
4. The method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1, Features The ceramic powder is titanium carbide, titanium diboride, titanium boride, silicon carbide or titanium nitride.
5. A method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1 or 4, Features The particle size of the ceramic powder is 0.5-3.0 μm.
6. A method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1 or 4, Features The ceramic powder accounts for 0.1-5.0wt.% of the composite powder.
7. The method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1, Features The low-energy ball milling parameters in step (2) are: rotation speed 180-220 r / min, time 4-6 h, ball-to-material ratio (2-3):
1.
8. The method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1, Features In step (3), the drying temperature of the vacuum drying oven is 80-120° C., and the drying time is 1-4 h.
9. The method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1, Features The printing parameters in step (4) are: laser power of 150-250 W, scanning rate of 900 mm / s-1200 mm / s, powder layer thickness of 30-50 μm, laser scanning spacing of 80-100 μm, and substrate preheating temperature of 100-200°C.
10. The method for preparing a 700°C resistant high-performance titanium-based composite material by using laser selective melting technology according to claim 1, Features In step (5), the annealing heat treatment temperature ranges from 800 to 1000° C., and the heat treatment time ranges from 1 to 4 hours.
Citation Information
Patent Citations
Method for preparing titanium-based nano composite material based on selective laser melting 3D printing
CN109943786A
Preparation method of in-situ nano TiB whisker-reinforced Ti-based composite material
CN111014669A
Preparation method of nano ceramic phase reinforced metal-based composite material
CN111961904A
Additive manufacturing method for nano-particle reinforced titanium-based composite material based on electron beam selective melting
CN113061779A
Rapid forming method for cylindrical part of 750 DEG C-resistant titanium-based composite material
CN113510242A
Cited By
Post-treatment method for high-toughness modification of molten titanium-based composite material of laser powder bed
CN120533116A
A post-processing method for high strength and toughness modification of laser powder bed fused titanium-based composite materials
CN120533116B
